(untitled) (American Journal of Pedagogical and Educational Research, 2022)
Experts of World Health Organization describe the growing prevalence of chronic diseases as a global epidemic of the XXI century. In recent years, special attention has been paid to diseases that are present in patients or occur on the basis of the underlying disease and are different from it.